Feminisme dan Anti-Feminisme: Bias Teologi Gender yang di (Salah) Pahami - Alfina Hidayah (BUANA GENDER : Jurnal Studi Gender dan Anak, 2020)
Feminism is a movement that was born and developed in the West until now it has been adopted by other developing countries, especially the Middle East and other Muslim-majority countries, resulting in various responses both who supported and against. The focus of this research is to examine feminism and the issue of gender equality, the development of feminism and muslim feminist, women in theology, theology of misogyny in holy verses, feminism and anti-feminism. The research method used is library research, therefore the data collected is representative library data wheras relevant to the object of research. So it can be concluded that both feminism and anti-feminism are not guaranteed to eradicate injustice, because basically men and women are not to be clashed and contested. But the real war is between justice and injustice, not men and women. So what needs to be fought is to call for goodness and prevent evil, not only for women but also for men who are oppressed even by women.